Factor XIII deficiency due to compound heterozygosity for 2 F13A1 variants - Jodie Odame; Caroline Malcolmson; Cindy Wakefield; Tammy Bourque; David Lillicrap; Orla Rawley; Mackenzie Bowman; Manuel Carcao; Vanessa Bouskill (Research and Practice in Thrombosis and Haemostasis)
Background: Factor (F)XIII deficiency is a rare bleeding disorder. Genomic studies, adjunctive to biochemical assays, can provide valuable diagnostic and clinical clarity. Key Clinical Question: We describe a case of a child with FXIII deficiency in which genomic studies were crucial for accurate diagnosis and treatment. Clinical Approach: An 8-year-old male presented with a severe bleeding phenotype. His FXIII antigen, activity, and alpha-subunit (FXIIIA) levels were below detection limits. Genetic analysis identified 2 likely pathogenic variants in F13A1: a novel nonsense variant (c.59_60del, p.Ser20X) and a missense variant (c.211G>A, p.Arg704Gln). Trio analysis revealed that compound heterozygosity for the p.Ser20X and p.Arg704Gln variants were causal for severe FXIIIA deficiency in the index case. Conclusion: Family segregation studies were essential in this case for interpreting genetic analysis results and identifying the causative variants resulting in severe FXIIIA deficiency.